2018
DOI: 10.1136/neurintsurg-2017-013507
|View full text |Cite
|
Sign up to set email alerts
|

What to do about fibrin rich ‘tough clots’? Comparing the Solitaire stent retriever with a novel geometric clot extractor in an in vitro stroke model

Abstract: Application of the GCE in this experimental stroke model to retrieve typically recalcitrant fibrin rich clots resulted in higher successful recanalization rates than the SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 17 publications
(7 reference statements)
3
51
0
Order By: Relevance
“…This finding is compatible with a clinical observation showing lower success in mechanical thrombectomy in the anterior circulation with large vessel angles 9. Fennell et al recently reported that hard clots were often dislodged in the tortuous carotid siphon by in vitro thrombectomy with the Solitaire stent 24. Machi et al also showed that elongation of the stent around a sharp curve reduced the interaction between the stent retriever and clot around the curve, resulting in dislodgement of the clot 23.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is compatible with a clinical observation showing lower success in mechanical thrombectomy in the anterior circulation with large vessel angles 9. Fennell et al recently reported that hard clots were often dislodged in the tortuous carotid siphon by in vitro thrombectomy with the Solitaire stent 24. Machi et al also showed that elongation of the stent around a sharp curve reduced the interaction between the stent retriever and clot around the curve, resulting in dislodgement of the clot 23.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, some studies have highlighted the relationship between hypodense thrombus in NECT and a high proportion of fibrin within the thrombi, which has been discussed as an important cause for poor outcome [15,16,29]. This finding is also consistent with recent findings on methodological difficulties of MT in fibrincontaining thrombi [23,24].…”
Section: Discussionsupporting
confidence: 80%
“…Current studies have shown that the performance of different MT methods is largely determined by the histological composition of the thrombus [23,24]. While current treatment strategies do not include the factor of thrombus composition, potential new individualized therapy methods for specific thrombi, for example, exactly those containing fibrin, are conceivable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been shown to be responsible for nearly half of unsuccessful procedures 16. Multiple variables are likely to govern device–thrombus interaction17 but patient factors associated with thrombectomy failure include fibrin rich18 or calcific emboli,19 intracranial atherosclerotic disease (ICAD),20 and vessel morphology 21…”
mentioning
confidence: 99%